EFEKTIVITAS PROGRAM KERJA INSTITUSI PENERIMA WAJIB LAPOR (IPWL) DALAM REHABILITASI PECANDU NARKOTIKA DI KABUPATEN AGAM - Muhammad Farid Yuanda; Dasman Lanin (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This article aims to describe the Effectiveness of The Work Program of Mandatory Reporting Institutions (IPWL) in the Rehabilitation of Narcotics Addicts in Agam Regency. This research uses descriptive qualitative method. The location of the research was conducted in Agam Regency precisely on Jln. Surau Usang, Jorong Parit Putus, Nagari Ampang Gadang, District IV Angkek.Informan research determined purposive sampling. This research data is obtained from interviews, observations, and documentation studies. Data validity test is done by trianggulasi source then data analyzed by reducing data, display data and drawing conclusions during the research. The results obtained after conducting the research, namely the Effectiveness of the Labor Compulsory Recipient Institution Work Program (IPWL) in the Rehabilitation of Narcotics Addicts in Agam District have been considered effective because it is successful in carrying out social rehabilitation activities of drug addicts. However, if assessed in terms of efficiency can be said still not optimal. In fact, drug addicts have stopped using drugs after completing rehabilitation activities at IPWL. However, they still have obstacles to re-mingle with the community as well as activities as usual, because of the image of an addict who is inherent and burdensome. Keywords: Effectiveness, IPWL Program, Rehabilitation of Narcotics Addicts